Implementasi Pembelajaran Berbasis STEM dalam Pendidikan Biologi untuk Meningkatkan Literasi Sains Siswa - Satria Bramantyo Putra; Rian Maheswara (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The implementation of STEM-based learning in biology education aims to enhance students' scientific literacy by integrating interdisciplinary approaches. This study investigates the effectiveness of STEM-based learning in improving students' understanding of biological concepts, problem-solving skills, and critical thinking. A quasi-experimental method was employed with a pre-test and post-test design involving high school students. The results indicate a significant improvement in students' scientific literacy, as evidenced by higher post-test scores and increased engagement in learning activities. The study highlights the potential of STEM-based learning to foster deeper comprehension and practical application of biological knowledge. These findings suggest that integrating STEM approaches in biology education can effectively support scientific literacy development among students.